Equity valuation Aurubis AG - Mayer, Moritz Gabriel Anton (2017)
The following thesis is written with the goal to give an equity valuation for Aurubis AG, a leading copper producer in Europe. The company has a unique business model along the vertical value chain. For that relevant theory is reviewed and later practical applied for the company. Here the Discounted Cash Flow method in combination with the Weighted Average Costs of Capital is used. Furthermore, a comparable analysis with trading multiples is created to check the plausibility of achieved results. Qualitative work is done with research about the industry, the demand and supply of copper as well as about Aurubis unique strengths, weaknesses and possible opportunities and threats. Based on these results a price of 54.6 € as fair value per share is reached. The result is compared with the equity research report of the bank M.M. Warburg`s Warburg Research division. The achieved equity value per share differs from the current market valuation as well as the research report and implies an overvaluation of the company.